ANALISIS PENGGUNAAN MODEL PEMBELAJARAN ABAD 21 PADA KEMAMPUAN KOGNITIF SISWA SEKOLAH DASAR - Nunung Noor Hayati; Wawan Shokib Rondli; Agus Darmuki (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to analyze the use of 21st century learning models on the cognitive abilities of students at SD 5 Kedungsari. The research method used is qualitative research, case study method. The subjects of the study were 6 class teachers taken using purposive techniques. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis is carried out using data reduction, data presentation, and conclusions. Based on the findings of data analysis that the 21st century learning model, namely project-based learning and collaborative learning is an effective strategy in improving the cognitive abilities of students at SD 5 Kedungsari. Therefore, this learning model must continue to be strengthened in learning, especially at SD 5 Kedungsari to ensure that students are ready to face challenges and succeed in an ever-changing era. Suggestions that must be considered to teachers in order to be able to apply 21st century learning models that suit the needs of students in the classroom.